Microstructure and durability properties of lightweight and high-performance sustainable cement-based composites with rice husk ash - Kaplan, Gökhan; Elmekahal, Mohamed A.Salem (Springer Science and Business Media LLC, 2021)
Abstract
Sustainable solutions are investigated to reduce the environmental damage caused by greenhouse gases and CO2 emissions. Cement is a construction material responsible for greenhouse gases and CO2 emissions. Thus, CO2 emissions are reduced by using replacement materials such as rice husk ash instead of cement. This study investigated the durability and mechanical properties of lightweight and high-performance, sustainable cement-based composites. A foaming agent was used to reducing the unit weight of the mixtures. Also, pumice powder (PP) and rice husk ash (RHA) were used to improve cement-based composites' durability and mechanical properties. The density of mixtures varies between 1666–2205 kg/m3. The early age strength of the mixes using 12.5% RHA has increased. The mixtures' compressive strength (91-days) with 25% RHA and 50% PP was 46.6 MPa. As the PP content of mixes increased, drying shrinkage values increased. Expansions decrease as the initial compressive strength increases in mixtures exposed to sulfate. As RHA and PP's ratio increased, weight loss decreased in mixes exposed to HCl, while weight loss increased in mixes exposed to H2SO4. It was determined that the content of CH(OH)2 is important in mixes exposed to HCl, and impermeability is important in mixes exposed to H2SO4. It has been observed that the initial compressive strength is also important in mixes exposed to the freeze-thaw effect. As the foam content of the mixes increased, the compressive strength decreased while the drying shrinkage increased. As a result, using up to 25% RHA has increased the performance of cement-based composites.
Keywords: Compressive Strength; Construction Materials; Sulfates; Oryza; 13. Climate action; 7. Clean energy; 12. Responsible consumption